A novel single input double output (SIDO) converter for torque ripple minimization in solar powered BLDC motor - Bapayya Naidu Kommula; Venkata Reddy Kota (International Journal of Renewable Energy Development, 2019)
This paper proposes a new converter topology for torque ripple reduction in Brushless DC (BLDC) motor. Due to the torque ripple problem, the use of this motor is limited to few applications. In this paper, a Single Input Double Output (SIDO) converter is proposed to suppress the torque ripple in BLDC motor. The proposed SIDO converter provides two output voltages. One for supplying the motor throughout conduction time and second output voltage is given to the non-commutating phase of motor during commutation instants. This proposed SIDO converter is fed from Photo Voltaic (PV) system. This paper also presents a new Maximum Power Point Tracking (MPPT) based on trisection of Power-Voltage characteristics (TPVC) to attain the maximum power from the PV system. This scheme takes only 7 iterations to reach MPP. The intended configuration is developed and simulated in Matlab/Simulink environment. The results justify the superiority of proposed scheme that minimizes torque ripple in BLDC motor to only 6 to 12% from 50 to 80 % in conventional scheme and also extracts maximum power from PV system. ©2019. CBIORE-IJRED. All rights reserved